Penyetelan Parameter Pengendalian Proses dengan PRC pada Sistem Pure-Capacitive-Two-Tank-in-Series dengan Pemanas di Tangki T-01 - Yulius Deddy Hermawan; Siti Diyar Kholisoh; Lili Suryani; Ramantasia Aktariastiwi Kusuma Putri (Seminar Nasional Teknik Kimia Kejuangan, 2016)
This researchcontinued the previous work by Hermawan, Y.D. et al., 2016. The goals of this research wereto tune the process control parametersand to do the closed loop dynamic simulationfor the proposed control configuration of Pure-Capacitive-Two-Tank-in-Series (PCTTS) with an electric heater in tank T-01.The proposed control configuration consisted of 3 couples of CV-MV as follows T1-qe, h1-vpu, and h2-f2. The open loop experiment results would be used for tuning of PID control parameters. In this work, the PID control parameters were tuned quantitatively by using Process Reaction Curve (PRC) method. The controllergain (Kc) for temperature control of tank T-01 (TC-01), level control of tank T-01 (LC-01), and level control of tank T-02 (LC-02) has been found as follows: 364.8 watt/oC, -2.3 volt/cm, and -12.9 cm2/second , respectively. The integral time constant (tI) for 3 controllers were as follows: 60 second, 60 second, and 90 second, respectively. The derivative time constant (tD) for 3 controllers were as follows: 15 second, 15 second, and 22.5 second, respectively. Furthermore, the proposed control configuration and resulted tuning parameters were examined through rigorous dynamic simulation by using scilab software. The input volumetric rate disturbance (with amount of ±29%) was made based on step function. The developed of closed loop state equation was solved numerically. Integral of the absolute value of the error (IAE) for TC-01, LC-1 and LC-2 were 73, 1686, and 695, respectively. The dynamic simulation results showed that the proposed control configuration with its tuning parameters gave a stable response to a change in the input volumetric rate. This study also revealed that the PID controller gave fastest responses compared to P and PI controller.